Approximate solution for Fokker-Planck equation - Drigo Filho, E.; Araujo, M.T. (Condensed Matter Physics, 2015)
In this paper, an approximate solution to a specific class of the Fokker-Planck equation is proposed. The solution is based on the relationship between the Schrödinger type equation with a partially confining and symmetrical potential. To estimate the accuracy of the solution, a function error obtained from the original Fokker-Planck equation is suggested. Two examples, a truncated harmonic potential and non-harmonic polynomial, are analyzed using the proposed method. For the truncated harmonic potential, the system behavior as a function of temperature is also discussed. У цiй статтi запропоновано наближений розв’язок спецiального класу рiвняння Фоккера-Планка. Розв’язок базується на зв’язку з рiвнянням типу Шредингера з частково обмеженим i симетричним потенцiалом. Щоб оцiнити точнiсть розв’язку, запропоновано функцiю похибок, яка отримана з оригiнального
рiвняння Фоккера-Планка. Використовуючи запропонований метод, проаналiзовано два приклади, а саме, утятий гармонiчний потенцiал i негармонiчний полiном. Окрiм цього, для утятого гармонiчного потенцiалу обговорено поведiнку системи в залежностi вiд температури.